Bysinosis: Occupational Lung Disease in The Textile Industry and Challenges in its Management - Vicennia Serly; Deddy Herman; Dessy Mizarti; Masrul Basyar (Eduvest - Journal of Universal Studies, 2025)
Byssinosis, also known as brown lung disease or Monday fever/Monday dyspnea, is a form of respiratory symptoms caused by exposure to raw non-synthetic textile materials during the production process in the industrial sector and is considered as a form of occupational lung disease. An increase in the prevalence of occupational lung diseases has been found in developing countries, particularly in South Asia. The etiology of byssinosis is the exposure to cotton dust in the textile industry, caused by exposure to endotoxins from the cell walls of gram-negative bacteria found in the dust of various plant fibers, including cotton. Diagnosing byssinosis requires taking a medical history, performing a physical examination, and conducting supporting examinations such as chest X-ray, high-resolution chest CT scan, and pulmonary function tests. In pulmonary function testing using spirometry, a decrease in the FEV1/FVC ratio may be observed. Based on clinical symptoms and lung function tests, the severity of byssinosis can be assessed using Schilling criteria. Inhalation medications such as short-acting and long-acting beta-agonists are choices for pharmacological management of byssinosis. Inhaled corticosteroids can be used in severe clinical conditions.